PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP BUDGETERY SLACK DENGAN JOB RELEVANT INFORMATION, OPPURTUNISTIC BEHAVIOR, DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL PEMODERASI - Tun Huseno (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2018)
This study aims to examine the effect of budgetary participation on budgetery slack with job relevant information, oppurtunistic behavior, and environmental uncertainty as moderating variables. This research is an explanatory research, which is a study that explains the relationship between variables through hypothesis testing. The data analyzed in this study were primary data collected through questionnaires containing a list of structured questions aimed at respondents who were selected purposively namely echelon IV and III officials in the tourism department, education offices, inspectorates, regional development planning agencies, cooperative and SMEs, numbering 70 people. The analysis technique used is the analysis of partial least square (PLS) based on variance. The results of this study are as follows: 1). Budgeting participation has a positive and significant effect on budgetary slack. 2). Job relevant information is not proven to moderate the influence of budgetary participation on budgetary slack. 3). Job relevant information has a positive and significant effect on budgetary slack. 4). Opportunistic behavior is not proven to moderate the effect of budgetary participation on budgetary slack and also has no significant effect on budgetary slack. 5). Environmental uncertainty is proven to moderate the influence of budgeting participation on budgetary slack and is pure moderation.